Fenofibrate-induced rhabdomyolysis in a patient with chronic kidney disease : an unusual presenting feature of hypothyroidism - Sousa, Alessandra Alves de (2009)
ABSTRACT: Clinical and most often moderate skeletal muscle involvement is a frequent problem in adults with hypothyroidism, and includes a number of different manifestations. Severe involvement with rhabdomyolysis, however, is very rare, and only a few cases have been reported to date, most of them with an additional factor of muscle injury. We described a patient with stage 3 chronic kidney disease who presented with rhabdomyolysis while taking fenofibrate, and was found to have hypothyroidism. We also highlighted the importance of excluding the diagnosis of thyroid dysfunction before treatment with lipid-lowering agents. _______________________________________________________________________________ RESUMO